2014
DOI: 10.1038/hr.2014.91
|View full text |Cite
|
Sign up to set email alerts
|

Deactivation of carotid body chemoreceptors by hyperoxia decreases blood pressure in hypertensive patients

Abstract: Previous studies have shown that hyperoxia-induced deactivation of carotid body chemoreceptors reduces sympathetic activity in hypertensive patients but it does not affect blood pressure. The maintenance of blood pressure can be explained by the direct, vasoconstrictive effect of hyperoxia, which offsets diminished sympathetic activity. This study compares the effect of acute hyperoxia on hemodynamic parameters between hypertensive and normotensive subjects. Twelve males with hypertension (age 39.4±2.4 years; … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

10
54
1
2

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 48 publications
(67 citation statements)
references
References 31 publications
10
54
1
2
Order By: Relevance
“…Hyperoxia, which silences peripheral chemoreceptors (Sinski et al. ), did not modify normalV˙E peak power and therefore normalV˙E oscillations in healthy subjects, in accordance with some but not all studies in patients with mixed sleep apnea (Brack et al. ).…”
Section: Discussionsupporting
confidence: 81%
“…Hyperoxia, which silences peripheral chemoreceptors (Sinski et al. ), did not modify normalV˙E peak power and therefore normalV˙E oscillations in healthy subjects, in accordance with some but not all studies in patients with mixed sleep apnea (Brack et al. ).…”
Section: Discussionsupporting
confidence: 81%
“…Despite the inevitable surgical damage to the mechanoreceptors and associated afferents, baroreceptor function improved. Also, in humans, brief exposure to oxygen lowers SBP, presumably due to sympathetic effects subsequent to inactivation of the chemoreflex 16 .…”
Section: Discussionmentioning
confidence: 99%
“…In human essential hypertensive subjects: a) the CBs are hypersensitive to chemical stimuli compared to those of their normotensive counterparts 13 , b) surgical CB removal reduces blood pressure (BP) in subjects with comorbid asthma 3, 14 and c) hyperoxia reduces BP in otherwise untreated subjects 15, 16 . A pivotal single-arm, unblinded trial testing the effects of surgical and interventional CB resection on human resistant HTN is ongoing in Europe (clinicaltrials.gov identifier: NCT01745172/NCT02099851).…”
Section: Introductionmentioning
confidence: 99%
“…177 It has also been shown that hyperoxia decreases BP acutely in patients with hypertension, but not in normotensive controls. 178 These data point to a potential pathogenetic role of tonic chemoreceptor drive in the development of sympathetic overactivity in hypertension. 177 Surgical removal of the CB has been performed in humans for reasons other than hypertension (eg, bronchial asthma and chronic obstructive pulmonary disease [COPD]).…”
Section: Carotid Body Ablationmentioning
confidence: 99%